Gross anatomical features of the insular cortex in affective disorders - Takahashi, Tsutomu; Sasabayashi, Daiki; Yücel, Murat; Whittle, Sarah; Suzuki, Michio; Pantelis, Christos; Malhi, Gin S.; Allen, Nicholas B. (Frontiers in Psychiatry, 2024)
IntroductionThe number of insular gyri is elevated in patients with schizophrenia. Thus, it has potential as a marker of early neurodevelopmental abnormalities. However, currently it remains unclear whether patients with other neuropsychiatric disorders, such as affective disorders, also have this gross brain anatomical feature.Materials and methodsThe macroscopic features of the insular cortex in 26 patients with bipolar disorder (BD), 56 with major depressive disorder (MDD), and control subjects for each clinical group (24 for BD and 33 for MDD) were assessed using magnetic resonance imaging.ResultsThe number of short insular gyri was higher in BD patients than in matched controls bilaterally with well-developed accessory and middle short gyri. Furthermore, the left middle short gyrus was more developed in MDD patients than in matched controls, and was weakly associated with the severity of depressive symptoms.DiscussionThe present results indicate that changes in the gross morphology of the insular cortex in BD and MDD is a potential vulnerability factor associated with their neurodevelopmental pathologies, and may also contribute to the severity of symptoms in MDD.